TMOD-25. LATENT SOX9-POSITIVE CELLS BEHIND MYC-DRIVEN MEDULLOBLASTOMA RELAPSE. (12th November 2021) - Borgenvik, Anna; Bolin, Sara; Savov, Vasil; Holmberg, Karl O; Zhao, Miao; Rosén, Gabriela; Hutter, Sonja; Garancher, Alexandra; Rahmanto, Aldwin Suryo; Bergström, Tobias; Mainwaring, Oliver; Sattanino, Damiana; et al.
Abstract: Tumor recurrence developing from therapy resistance, immune escape and metastasis is the leading cause of death in medulloblastoma, the most frequent malignant pediatric brain tumor. Amplification of MYC genes is the most common genetic alteration in Group 3 and Group 4 subgroups that constitute two thirds of medulloblastoma. SOX9 is a transcription factor present in stem cells in the normal brain but is limited to rare, quiescent cells in medulloblastoma patients with MYC gene amplifications. By studying paired primary-recurrent patient samples and patient-derived xenografts we here identified significant accumulation of SOX9-positive cells in Group 3 and Group 4 relapses. To follow relapse at the single cell level we developed an inducible dual Tet model of MYC-driven MB, where MYC was re-directed from the treatment-sensitive bulk cells to resistant, dormant SOX9-positive cells by doxycycline. In this model, distant recurrent tumors and spinal metastases developed. SOX9 promoted immune escape, DNA repair suppression and was essential for recurrence. Tumor cell dormancy was non-hierarchical, migratory and depended on MYC suppression by SOX9 to promote relapse. By using computational modeling and treatment we also showed how doxorubicin and MGMT inhibitors were specifically targeting recurrent cells that could be of potential use in future treatments for patients affected by these fatal relapses.